Fine specificity of anti MSP 119 antibodies an multiplicity of Plasmodium falciparum merozoite protein 1 types in individuals in Nigeria with submicroscopic infection (2010)
Background: The absence of antibodies specific for the 19 kDa C-terminal domain of merozoite surface protein 1 (MSP119) has been associated with high-density malaria parasitaemia in African populations. The hypothesis that a high prevalence and/or level of anti-MSP119 antibodies that may inhibit erythrocyte invasion would be present in apparently healthy individuals who harbour a sub-microscopic malaria infection was tested in this study. Methods: Plasma samples were collected from residents in a region in Nigeria hyperendemic for malaria, who had no detectable parasitaemia by microscopy. Using a competition-based enzyme-linked-immunosorbent assay with two invasion-inhibitory monoclonal antibodies (mAbs) 12.10 and 12.8, the levels and prevalence of specific antibodies were measured. The minimum multiplicity of infection was determined using PCR. The prevalence of anaemia was also measured. Results: Plasma samples from 85% of individuals contained antibodies that bound to MSP119. The inhibition of mAb 12.10 binding was strongly correlated with the prevalence (Spearman correlation test, p < 0.0001) and mean titre of anti-MSP119 antibodies (Spearman correlation test, p < 0.001) in the samples. Comparing samples from individuals with multiple infection (group M) and single infection (Group S), group M contained a higher (p = 0.04) prevalence of anti-MSP119 antibodies that competed with mAb 12.10. Using a logistic regression model, it was found that the presence of antibodies competitive with mAb 12.10 was affected negatively by anaemia (p = 0.0016) and positively by the carriage of multiple parasite genotypes (p = 0.04). Conclusions: In the search for correlates of protection against malaria, which will be essential to evaluate clinical trials of malaria vaccines based on MSP1, this study examines some potential assays and the factors that need to taken into account during their evaluation, using samples from individuals naturally exposed to malaria infection.